Fabrication techniques and morphological analysis of perovskite absorber layer for high-efficiency perovskite solar cell: A review. (December 2018) - Jamal, M.S.; Bashar, M.S.; Hasan, A.K. Mahmud; Almutairi, Zeyad A.; Alharbi, Hamad F.; Alharthi, Nabeel H.; Karim, Mohammad R.; Misran, H.; Amin, Nowshad; Sopian, Kamaruzzaman Bin; Akhtaruzzaman, Md.
Abstract: Organolead trihalide perovskite absorber layers are potential contenders in solar energy harvesting technologies because of their competitive lower fabrication cost, high power conversion efficiency, and ease of processing. The structural, interfacial and morphological properties are the key aspects to determine the stability and photon-to-current conversion efficiency of Perovskite solar cells (PSCs). Most contemporary research has emphasised on enhancing the power conversion efficiency (PCE) of perovskites by changing the fabrication process, solvent engineering, or precursor solution. With changes in these variables, the structure and morphology of perovskites also change, which affects the photon-to-current conversion efficiency and the stability of the PSCs. However, no stockpiled records have aided in conducting corresponding research outcomes on this perspective. In this review, we summarise the effect of fabrication method on the structure and morphology, as well as the PCE and stability of PSCs. This review will help readers decipher the scientific and technological challenges concerning hybrid inorganic–organic PSCs. Highlights: Deposition technique controls the structure and morphology of the perovskite layer and PCE of PSCs. Pinhole and slower crystallisation were challenged for OSD method. Inequality of grain size and surface smoothness is one of the shortcomings of SDM method. Extremely uniform surface coverage, pinhole free and large grain size were obtained by TVD method The CVD method has been widely used in the commercial deposition techniques.